Expression of Potential Dermal Progenitor Cell Markers in the Tumour and Stroma of Skin Adnexal Malignant and Benign Tumours - Sven R. Quist; Maximilian Eckardt; André Kriesche; Harald P. Gollnick (Stem Cells International)
Stem cells are multipotent cells that maintain the skin epidermis including skin appendages such as hair follicle, sebaceous glands, and sweat glands. There is evidence that reciprocal signalling between the epidermis and the dermis plays an important role in skin development, homeostasis, wound repair, and skin cancer. The origin of skin cancer that derive from skin appendages is still controversial, including basal cell carcinoma and even more of rare tumours such as sebaceous carcinomas and whether those tumours originate from resident tissue stem cells. To investigate whether markers reported to label dermal progenitor cells are preserved in the tumour including the tumour stroma of skin adnexal tumours, we tested 45 human basal cell carcinomas, including superficial, nodular, adenoid, infiltrating, and sclerosing types, and further 38 human tumours of skin appendages including 13 sebaceous adenomas and carcinomas, 20 eccrine sweat gland tumours, and 5 pilomatricomas, syringomas, and hair follicle tumours for the expression of the potential dermal and epidermal cell markers CRABP1, Nestin, and Ephrin B2 and compared these findings with healthy, age-related human epidermis. We detected that CRABP1, Nestin, and Ephrin B2 are expressed in the intratumoural stroma as well as the tumour invasive front of skin tumours of appendages and BCCs.